Beban Kerja dan Manajemen Talenta Terhadap Kinerja Karyawan - NOVITASARI, MAFIDA (Jurnal Ilmu Manajemen (JIM), 2019)
PT. Surabaya Industrial Estate Rungkut is one of the State-Owned Enterprises (SOE) engaged in the development and management of industrial estates along with supporting facilities. The Achieving organizational goals can be supported by good Employees Performance. The Faktors that may affect Employees Performance are Workload and Talent Management. The objectives of this research to examine and analyze the influence of Workload and Talent Management on Employee Performance at PT. Surabaya Industrial Estate Rungkut. This type of research is causal and inferential with a quantitative approach method. The sample in this research amounted to 57 employees of PT. Surabaya Industrial Estate Rungkut who has participated in the Talent management program with saturated sampling techniques. statistical analysis used in this research is multiple linier regression with the assistance software SPSS version 19 program. The results of this research explain the Workload partially has a negative effect on Employee Performance, Talent Management partially has a positive effect on Employee Performance, Workload and Talent Management simultaneously influencing Employee Performance. Keywords: employee performance; talent management; workload.